2020
DOI: 10.1101/2020.05.29.124008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TowardsMycobacterium tuberculosisdetection at the point-of-care: a brighter solvatochromic probe permits the detection of mycobacteria within minutes

Abstract: 25There is an urgent need for point-of-care tuberculosis (TB) diagnostic methods that are fast, 26 inexpensive, and operationally simple. Here, we report on a bright solvatochromic dye trehalose 27 conjugate that specifically detects Mycobacterium tuberculosis (Mtb) in minutes.3-28 hydroxychromone (3HC) dyes, known to yield high fluorescence quantum yields, exhibit shifts in 29 fluorescence intensity in response to changes in environmental polarity. We synthesized two 30 analogs of 3HC-trehalose conjugates … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…This allowed the detection of Mtb cells within 10 minutes of treatment and may well represent a major step towards on-site testing for Mtb infection. 111 Hodges et al recently reported the use of a different strategy for fluorogenic Mtb cell wall detection. Their approach employs a trehalose variant dubbed "quencher-trehalosefluorophore" (QTF, Fig.…”
Section: Organic and Biomolecular Chemistrymentioning
confidence: 99%
“…This allowed the detection of Mtb cells within 10 minutes of treatment and may well represent a major step towards on-site testing for Mtb infection. 111 Hodges et al recently reported the use of a different strategy for fluorogenic Mtb cell wall detection. Their approach employs a trehalose variant dubbed "quencher-trehalosefluorophore" (QTF, Fig.…”
Section: Organic and Biomolecular Chemistrymentioning
confidence: 99%
“…73,96,97 Such detectable trehalose-based imaging probes have proven valuable for answering fundamental questions about mycobacterial cell envelope structure and metabolism, 60, 65, 66, 98-107 and are currently being pursued as tools for anti-mycobacterial drug development 47,108 and imaging of mycobacterial infections. 94,[109][110][111] Although progress on trehalose-based imaging probes over the last decade has been swift and exciting, a remaining impediment to the creation and adoption of these tools has been limited access to existing probes and the development of new probes. Chemoenzymatic synthesis has played an important role in addressing these problems, an illustrative example of which relates to the earliest trehalose analogues reported for imaging mycobacteria, FITC-Tre and the "clickable" TreAz series of analogues (structures shown above in Figure 4).…”
Section: Imaging Mycobacteria With Trehalose Analoguesmentioning
confidence: 99%
“…Some fluorogenic trehalose probes, synthesized via 6-TreAz as an intermediate, have even been shown to rapidly detect M. tuberculosis in patient sputum samples, demonstrating potential as point-of-care diagnostic tools. 109,110 However, these probes rely on optical imaging and thus are not suitable for specific in vivo imaging of mycobacteria in patients. Such a capability is not yet available but could transform how M. tuberculosis infections are managed in the clinic, including challenging cases involving recurrence, drug resistance, or disseminated disease.…”
Section: Imaging Mycobacteria With Trehalose Analoguesmentioning
confidence: 99%
“… 12 , 13 New fluorescent probes have been developed to report on the activity of mycobacterial enzymes. For example, probes have been developed that target mycobacterial esterases, 14 sulfatases, 15 and trehalose mycolyltransesterases, 16 , 17 but these probes are nonspecific since they also label nontuberculous mycobacteria (NTMs) that may also be present in sputum. Probes activated by the Mtb β-lactamase BlaC have been shown to specifically label Mtb in patient sputum samples.…”
Section: Introductionmentioning
confidence: 99%